Investigating the Need of Students in Developing a Model of Web 2.0-Based Extensive Listening Materials - Surti Milarisa; Abdurrachman Faridi; Rudi Hartono; Frimadhona Syafri (Universitas Negeri Semarang, 2022)
Learning English especially for listening is still considered as challenging area. It is due to the unavailability of suitable material of listening which is in accordance to the students’ needs. Moreover, students face the difficulty in listening, because they have no sufficient background about listening in their previous school. Therefore listening remains untouched in English teaching. Moreover, this study attempts to investigate the need analysis in developing a model of web 2.0-based Extensive Listening (EL) materials by students' need. This study applied a descriptive qualitative method in analyzing data. The questionnaires was used for collecting the data from 68 students in English Department in Berau, East Kalimantan. The results showed that 82.2% students chose the authentic materials for learning extensive listening. The finding also showed that the 86.9% students agree with web-based as a tool for extensive listening. The most of students chose fiction as a material for EL as Listening for pleasure learning. The students need to listen several of activities of listening; for instance: folklores such as history of the kingdom from the education web.